Price setting behaviour in the Netherlands: results of a survey - Ad C.J. Stokman; Marco M. Hoeberichts (European Central Bank (ECB), 2006)
This paper presents the results of a survey among Dutch firms on price setting behaviour in the Netherlands. It aims to identify how sticky prices are, which prices are sticky and why they are sticky. It is part of the Eurosystem Inflation Persistence Network (IPN). The most distinctive feature of the Dutch survey is its broad coverage of the business community (seven sectors and seven size classes). Our primary finding is that price setting behaviour depends critically on both a firm's size and the competitive environment it faces. Small firms in particular adopt more rigid pricing policies, and the weaker the competition a firm faces, the stickier a company's price will be. Furthermore, we find that wholesale and retail prices are more flexible than those for business-to-business services. The survey suggests that explicit and informal contracting are the most important sources of price stickiness. Menu costs and psychological pricing – two prominent explanations of price stickiness in the literature – are of minor importance. Finally, there is clear evidence of asymmetries in shocks driving price increases and decreases.
Keywords: E30; D40; 330; nominal rigidity; price setting; survey data; Preismanagement; Preisrigidität; Niederlande